'It was like navigating uncharted waters': exposing the hidden capitals and capabilities of the graduate marketplace. Issue 2 (4th March 2023) - O'Shea, Sarah
ABSTRACT: Differentials in graduate employment outcomes are pervasive across Australian higher education. Workforce participation is not evenly distributed across student cohorts, and learners disadvantaged by material resources or geographic location remain under-represented in overall employment rates. This inequity demands in-depth and systematic analysis that considers lived experience of navigating the transition between university and the workplace. This article reports on findings from a 2019 study with Australian graduates, which focused on those learners who were the first in their immediate family to participate in university. The findings point to the diversity of capitals and capabilities that participants drew upon to successfully navigate the postgraduate market. Drawing upon a capital/capability theoretical framing provides insight into the ways in which university staff and policymakers can recognise and leverage the existing strengths of learners to better prepare individuals to achieve their 'fertile' functioning within the contemporary graduate landscape.